Analisis Efektivitas Penerapan Metode Pembelajaran Tari di RA Fatipa - Hilda Zahra Lubis; Amanah Putri Fadillah; Andina Zahra; Fannia Sri Juwita; Nia Alfiyalawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study analyzes the effectiveness of dance learning methods at RA Fatipa on early childhood development. This descriptive qualitative study used classroom observations, interviews with teachers and principals, and documentation to collect data. The results showed that dance learning methods at RA Fatipa were effective in improving cognitive, physical-motor, social-emotional, creativity, and character aspects of children. However, limited facilities and infrastructure, teacher training needs, and parental support are obstacles. This study recommends improving facilities and infrastructure, ongoing training for teachers, and closer cooperation between schools and parents to optimize the benefits of dance learning for children's holistic development.